Evaluasi Ekonomi Total Hip Arthroplasty Protokol Enhance Recovery After Surgery Dibandingkan Konvensional di RSUP Fatmawati Jakarta - Lumbangaol, Hanna Elisabet; Nadjib, Mardiati (UI Scholars Hub, 2024)
Total hip arthroplasty (THA) is a common orthopedic procedure performed to replace damaged hip joints with prostheses. The demand for this procedure is expected to rise in the future. Enhanced Recovery After Surgery (ERAS) has been introduced as an evidence-based, multidisciplinary approach aimed at optimizing postoperative recovery and reducing hospital length of stay. This study aims to evaluate the costs and effectiveness, including hospital stay duration and surgical success rates, of THA using the ERAS protocol compared to conventional approaches. This cross-sectional study involved data collection from healthcare providers between January 2020 and May 2023. The analysis showed that both protocols achieved a 100% success rate in surgery, while a length of stay of ≤5 days was recorded in 88% of ERAS cases and 75% of conventional cases. The average costs were IDR 41,525,202 for the ERAS protocol and IDR 40,845,242 for the conventional protocol. Although no statistically significant differences were found in the direct medical costs or effectiveness between the two approaches, the primary cost differences were attributed to physician consultation and diagnostic examinations. This study was limited to cost and effectiveness analyses, without a comprehensive cost-effectiveness evaluation, such as calculating cost-effectiveness ratios. These findings provide initial insights into the economic implications of the ERAS protocol in Indonesian hospital settings.